1.13=p-1.3

Simple and best practice solution for 1.13=p-1.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.13=p-1.3 equation:


Simplifying
1.13 = p + -1.3

Reorder the terms:
1.13 = -1.3 + p

Solving
1.13 = -1.3 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
1.13 + -1p = -1.3 + p + -1p

Combine like terms: p + -1p = 0
1.13 + -1p = -1.3 + 0
1.13 + -1p = -1.3

Add '-1.13' to each side of the equation.
1.13 + -1.13 + -1p = -1.3 + -1.13

Combine like terms: 1.13 + -1.13 = 0.00
0.00 + -1p = -1.3 + -1.13
-1p = -1.3 + -1.13

Combine like terms: -1.3 + -1.13 = -2.43
-1p = -2.43

Divide each side by '-1'.
p = 2.43

Simplifying
p = 2.43

See similar equations:

| -4-4n=1-5n | | x+6*x-9=30 | | 3[x-2]=27 | | 2y=2y+44 | | 40+4x=12(x+20) | | 5-8m=14-5m | | 1.7-x=1.2 | | g/-4=-4.21 | | x+6x*-9=30 | | 5x^4-40x^2=0 | | M+23=94 | | 5k+4=3k-2k | | 3.1=x-1.5 | | 4/6r=5 | | x+6a*-9=30 | | 3n-n=4+n | | x=10*log(100) | | x-0.6=1.1 | | g-4= -4.21 | | 4z+5=6z-3z | | r/2=-18 | | -28=-2(w+7) | | x=1000*log | | -12+8n=-2n+4n | | u=2u-64 | | 12n+20=(n+5)*7 | | -4k=-19.6 | | c=40+55h | | 14x-5=12x-5 | | (n-5)*6=3n-6 | | 2.6+10m=8.29 | | -2(x+2)=4-(5x-7) |

Equations solver categories